The evolving law on sexual and reproductive health rights and the right to abortion in Kenya - Aliongo, Sara Ayoti Mate (Department of Public Law, 2022)
Article 26(4) of the Constitution of Kenya guarantees the right to abortion in these circumstances: ‘where there is danger to the life of the mother; where there is danger to the health of the mother; if there is need for emergency treatment of any kind; and if allowed by any other written law.' Accordingly, this dissertation argues that the jurisprudence of international and regional human rights bodies demonstrates that the right to abortion is a justiciable human right. Therefore, it probes whether Kenya is honouring her state obligation to respect, promote and fulfil the right to abortion as a human right as guaranteed in the Constitution and international law obligations. Furthermore, it analyses Kenyan law and policy on the right to abortion and assesses whether Kenya's law on abortion is a barrier to the effective realization of the right to abortion. To investigate whether safe abortion is accessible to Kenyan women and a realizable human right in Kenya, the dissertation examines the Constitution, legislation and government policies on access to abortion vis-à-vis the reality and experiences of Kenyan women accessing safe abortion. The dissertation finds that the subsisting contradiction between the constitution and the penal code provisions on access to abortion reinforced by inconsistent policies from the government of Kenya continues to exacerbate unsafe abortion in Kenya thus hindering the effective realisation of the right to abortion in Kenya. The study compares how South Africa, has implemented its progressive law on the right to abortion and the insights that Kenya could draw from the South African experience.The study concludes by appealing to Kenya to ensure the effective realisation of the right to abortion by revoking the punitive clauses of the penal code, aligning laws and government policies with Article 26(4) of the Constitution, enacting the Reproductive Healthcare Bill that will expand access to abortion and educating Kenyans on the current permissive legal provisions on access to safe abortion.